Temperature Anomaly and Severe Cyclone Events in the Southern Coastal Regions of Bangladesh (Journal of Environmental Science and Natural Resources, 2015)
Bangladesh is a disaster prone country where cyclone occurs more frequently in recent decades. In this study, 52 cyclone events observed mainly in the southern coastal regions of Bangladesh from 1960 to 2010 were considered. Extreme weather data were obtained from Disaster Preparedness Centre, AIT and Bangladesh Bureau of Statistics. NCEPNCAR reanalysis data were used to find out the distribution of temperature anomaly over Bangladesh and Bay of Bengal (BB). Skew-T Log-P analysis is done to assess vertical instability of upper atmosphere. The results suggest the prevalence of severe cyclones like category 3 to 5 is mostly from September to December, which are increasing since last two decades. The Skew-T Log-P analysis derived instability indices like CAPE, CIN, KI, LI, and SHOW are very useful to assess extreme weather phenomena. But the strongest signal behind severe cyclone formation over BB is the formation of relatively cooler zone (strong negative anomaly) near to surface level, whereas at the same time the upper atmosphere was dominated by the development of relatively warmer zone (strong positive anomaly).J. Environ. Sci. & Natural Resources, 8(1): 35-40 2015